Time-dependent mechanical behavior of sweet sorghum stems. (June 2020) - Lee, Seunghyun; Zargar, Omid; Reiser, Carl; Li, Qing; Muliana, Anastasia; Finlayson, Scott A.; Gomez, Francisco E.; Pharr, Matt
Abstract: Grasses represent the most productive and widely grown crop family across the globe but are susceptible to structural failure (lodging) during growth (e.g., from wind). The mechanisms that contribute to structural failure in grass stems are poorly understood due to a lack of systematic studies of their biomechanical behavior. To this end, this study examines the biomechanical properties of sweet sorghum ( Sorghum bicolor (L.) Moench), focusing on the time-dependent behavior of the stems. Specifically, we conducted uniaxial compression tests under ramp and creep loading on pith and stem specimens of the sorghum cultivar Della. The tests demonstrated significantly nonlinear and time-dependent stress-strain behavior in all samples. We surmise that this behavior arises from a combination of poroelasticity due to migration of water through the plant and viscoelasticity due to rearrangement of macromolecular networks, such as cellulose microfibrils and lignin matrices. Overall, our measurements demonstrate that sorghum is not a simple reversible elastic material. As such, a complete understanding of the conditions that lead to stem lodging will require knowledge of sorghum's time-dependent biomechanical properties. Of practical importance, the time-dependent biomechanical properties of the stem influence its mechanical stability under various loading conditions during growth in the field (e.g., different wind speeds).